THE EMBLEMATIC DISCOURSE MARKERS LAH IN COLLOQUIAL SINGAPOREAN ENGLISH - Inharjanto, Anselmus (The Journal Of English Teaching For Young And Adult Learners, 2024)
This research aims to investigate the emblematic discourse markers lah in Colloquial Singaporean English (CSgE). The questions addressed are why the lah particle is commonly used as a discourse marker in CSgE and to what extent it contributes to the analysis and description of discourse markers in English language. This descriptive qualitative study explores empirically and theoretically the topic grounded on the secondary sources. The involvement of a related-literature review from previous researchers and experts, written in some journal articles and scientific books, has been considered. The result of the study demonstrates that the particle lah is indeed commonly used as a discourse marker by Singaporeans and identified as one of the most emblematic discourse markers in CSgE. The notion of diglossic situation seems to be one of the reasons why lah is widely used among Singaporeans. The pragmatic function of lah is noticeable as well since it is used to indicate emphasis, solidarity, familiarity and informality. Finally, the particle lah surely contributes to the analysis and description of discourse markers because it represents a naturally-occurring example of English in use. So, lah may enrich the English grammar, highlight its pragmatic function, and demonstrate the variability of English.